A Toolkit for Women Migrant Workers' Empowerment in Malaysia: Meeting Sexual and Reproductive Health Needs - Miles, Lilian; Lewis, Suzan; Endut, Noraida; Lai, Wan Teng; Yasin, Suziana Mat; Ying, Kelvin (Centre for Research on Women and Gender, 2018)
Malaysia continues to be one of the largest importers of labour in Asia. Women migrant workers constitute a significant workforce in its manufacturing, service and domestic sectors. It is estimated that women constitute almost 40 percent of its migrant population today1. Women migrant workers work under severe and punitive conditions in Malaysia, with few rights and entitlements at work and in their communities. In this toolkit, we focus on advancing their sexual and reproductive health. Women’s migration has wide-reaching implications for their sexual and reproductive health, but this aspect of their health has not attracted sufficient attention by the government, employers, health care providers, civil society or researchers in Malaysia. There is a lack of gender-sensitive policies overall, to address these needs and protection of this aspect of health and well-being is minimal. Consequently, little is known about the difficulties these women face in coping with sexual and reproductive health illnesses or when seeking treatment, or of interventions which can meet their sexual and reproductive health needs.